AL-ASHIL WA DAKHIL FI TAFSIR - Rofiq Junaidi (UIN Raden Mas Said Surakarta, 2014)
The Qur'an is primary source for the life of Muslimsbesides the hadith from the Prophet Muhammad PBUH. As a Moslem,following the guidance of Allah and His messenger that explained inthe Qur'an and Sunnah is an obligation. Qur'an declared itself to behudan linnas for all divines in religious teachings. Its teachingscontained in the stories either explicitly or implicitly so that people cantake the lessons. In addition it also contains general rules, globlprinciples, including verses of muhkamat and mutashabihat.Everything was revealed by Allah through his messenger ProphetMuhammad PBUH and was subsequently conveyed to mankind. TheMoslems are aware to get Allah‟s guidance and His taufiq. They haveno glory except heading towards to the Qur'an and Sunnah. However,the messages that Allah sent down to His messengers often getblasphemies even tahrif from the followers in terms of both the textsand the meaning. All messages were distorted by those who follow theirdesires except the holy book of the Koran (Al-Qur‟an). Allahguaranteed the authenticity of its contents until the judgment day(yaum el Qiyamah). In keeping the authenticity of the Qur'an in 'Ulumal-Qur'an (Sciences of the Qur'an), there is a subject knowledge thatserves as „cleaning‟ and „sterilizing‟ the Qur'an from the things that arenot true in Koran teachings. The subject is known as Ad-Dakhil